Characterization of the far-red light absorbing light-harvesting chlorophyll a/b binding complex, a derivative of the distinctive Lhca gene family in green algae - Kosugi, Makiko; Ohtani, Shuji; Hara, Kojiro; Toyoda, Atsushi; Nishide, Hiroyo; Ozawa, Shin-Ichiro; Takahashi, Yuichiro; Kashino, Yasuhiro; Kudoh, Sakae; Koike, Hiroyuki; Minagawa, Jun (Frontiers in Plant Science, 2024)
Prasiola crispa, an aerial green alga, exhibits remarkable adaptability to the extreme conditions of Antarctica by forming layered colonies capable of utilizing far-red light for photosynthesis. Despite a recent report on the structure of P. crispa’s unique light-harvesting chlorophyll (Chl)-binding protein complex (Pc-frLHC), which facilitates far-red light absorption and uphill excitation energy transfer to photosystem II, the specific genes encoding the subunits of Pc-frLHC have not yet been identified. Here, we report a draft genome sequence of P. crispa strain 4113, originally isolated from soil samples on Ongul Island, Antarctica. We obtained a 92 Mbp sequence distributed in 1,045 scaffolds comprising 10,244 genes, reflecting 87.1% of the core eukaryotic gene set. Notably, 26 genes associated with the light-harvesting Chl a/b binding complex (LHC) were identified, including four Pc-frLHC genes, with similarity to a noncanonical Lhca gene with four transmembrane helices, such as Ot_Lhca6 in Ostreococcus tauri and Cr_LHCA2 in Chlamydomonas reinhardtii. A comparative analysis revealed that Pc-frLHC shares homology with certain Lhca genes found in Coccomyxa and Trebouxia species. This similarity indicates that Pc-frLHC has evolved from an ancestral Lhca gene with four transmembrane helices and branched out within the Trebouxiaceae family. Furthermore, RNA-seq analysis conducted during the initiation of Pc-frLHC gene induction under red light illumination indicated that Pc-frLHC genes were induced independently from other genes associated with photosystems or LHCs. Instead, the genes of transcription factors, helicases, chaperones, heat shock proteins, and components of blue light receptors were identified to coexpress with Pc-frLHC. Those kinds of information could provide insights into the expression mechanisms of Pc-frLHC and its evolutional development.